Konsep Waris Berdasarkan Gender Dan Keadilan Dalam Kitab Melayu Is’af Al Khaaid Karya Syekh Muhammad Syukri Unus Al-Banjari - Ali Mu’ammar (PT. Sharia Journal and Education Center, 2024)
Abstract This research explores the concept of inheritance based on gender and justice as presented in the Malay manuscript